Sensitive detection of PIK3CA Exon 20 H1047R breast cancer based on lowcost intercalary dye SYBR Green I real-time qPCR assay - Desriani; Azamris; Rustamadji, Primariadewi; Abna, Inherni Marti; Ibadurrahman, Irsyad; Fuad, Asrul Muhammad; Nurdiani, Dini; Yuliawati, Yuliawati; Herawati, Neng; Fitria, Najmiatul; Warisman, Muhammad Ali; Utami, Nuruliawaty (Penerbit Universiti Kebangsaan Malaysia, 2024)
Breast cancer is associated with an excessive function of somatic mutation in phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α (PIK3CA), specifically in exon 9 and 20 hotspots. Exon 20, which contains H1047R, has more potential for an oncogenic mutation than exon 9. Detection of PIK3CA/H1047R mutation has also been reported for molecular diagnosis and therapeutic application. Sensitive methods are required because mutants are mostly present at low levels in a mixture with the wild type. Therefore, this study aimed to explore the development of a low-cost and sensitive PIK3CA exon 20 H1047R detection method using intercalary dye real-time qPCR (quantitative polymerase chain reaction), SYBR Green I. The method was primer design, formulation, specificity, limit of detection, reproducibility, repeatability, and genotyping of 15 DNA (deoxyribonucleic acid)-frozen tissue patient samples, which were further confirmed by PCR sequencing for validation. DNA primer proportion formulations were 0.25 μM PIK3CA exon 20 (WT), 0.65 μM PIK3CA exon 20 H1047 (MT), and 0.2 μM reverse primer in 10 μl total volume. The results showed that compared to the gold standard genotyping PCR sequencing (6.6-20%), the developed method had a higher sensitivity of 5%. The coefficients of intra- and inter-variability were between 0.01-0.19%, suggesting the developed method was repeatable and reproducible with a low mean pipetting error. Genotyping of 15 DNA breast cancer patient samples showed a wild-type genotype, which was in 100% agreement with the PCR sequencing result. The developed method showed sensitive, reproducible, and repeatable results, potentially applicable in prognosis and therapeutic predictions.